Effects of Additive Materials on Indirect Tensile Strength and Moisture Sensitivity of Recycled Asphalt Pavement (RAP) - Ebrahim, Soz Mohammed; Kamal Karim, Hardy (Kurdistan Journal of Applied Research, 2019)
Using reclaimed asphalt pavement with additives as part of new road construction has economic and environmental advantages. As an attempt to preserve aggregate resources and save money, and knowing the effects of the selected additive materials, this study was done in Sulaimani City. The samples of the RAP were selected from the Sulaimani municipality stockpiles. The ignition and centrifuge testing machines were used to separate the aggregate and binder of the RAP. Based on the standard deviation of the obtained asphalt content, the blend was decided to be 40% RAP and 60% new material. The aggregate tests were conducted to evaluate the characteristics of the PAR aggregate. The performance grade test was done for the reclaimed asphalt binder. Three types of additives, which were Styrene Butadiene-Styrene (SBS), Crumb Rubber (CR), and Polypropylene (PP), mixed with the reclaimed asphalt binder with three different percentages of the binder which were 3%, 5%, and 7%. Indirect Tensile Strength (ITS) test was performed to the conditioned and unconditioned mixtures. To evaluate the effects of additives on the moisture sensitivity of the reclaimed mixtures, ITS Ratios were obtained. Most of the percentages of additives decreased the ITS of the conditioned and unconditioned samples. The only percentage of the additive material increased the ITS was 5% of PP in conditioned case. However, additives did not benefit the ITS, they benefited the ITSR greatly. The best obtained ITSR for each additive material was 7% SBS, 3% CR, and 5% PP that had 99.71%, 97.1%, and 90.7%, respectively.